CAA simulations of the leading edge noise of a heaving airfoil. (28th April 2020) - Sun, Yuhao; Zhong, Siyang; Zhou, Teng; Huang, Xun; Zhang, Xin
Abstract: Leading edge noise of airfoil is a significant source of broadband noise for both aircraft and wind turbines. In this work, the noise generated by the interaction of incoming turbulence and a heaving airfoil was studied. Numerical experiments were performed using a hybrid computational aeroacoustics method, where the mean flow was computed by using computational fluid dynamics, and the acoustic field was obtained by solving the linearised Euler equations. Applying Fourier analysis, the periodic mean flows around the heaving airfoil can be accurately reproduced for the aeroacoustic simulations. The incoming isotropic and anisotropic turbulence was synthesised by a modified digital filter method. The effect of the heaving motion on the leading edge noise was evaluated through the comparisons of far-field directivities and noise spectra. The far-field noise results indicate that the effect of airfoil heaving motion on the leading edge noise is larger if the incoming turbulence is anisotropic. For turbulence with a larger integral length scale in the streamwise direction, more noise is produced, while less noise is generated when the larger integral length scale is in the transverse direction. It is expected that the proposed method and numerical results can be helpful in providing physical insights into the airfoil leading edge noise under realistic conditions. Highlights: A hybrid method is developed for the leading edge noise of a heaving airfoil. The numerical results suggest that the inviscid mean flow assumption is invalid. The effect of the heaving motion is larger for anisotropic turbulence. The increase or decrease in noise depends on the direction turbulence is stretched.